Decentering social theory - Go, Julian, 1970- (Bingley, U.K. : Emerald, 2013)
Social theory and research has long faced the limitations of its conventional Eurocentric focus. The essays in this volume offer new thoughts and empirical studies for transcending those limitations. A continuation of PPSTs previous volume on "postcolonial sociology", this volume, "Decentering social theory," questions old categories, advances new postcolonial themes in social science, and debates alternative theoretical paradigms. The "scholarly controversies" section contains a critical exchange on "southern theory" between Raewyn Connell and Patricia Hill Collins, Mustafa Emirbayer, Raka Ray and Isaac Ariail Reed.
Ambiguities of democratization : nationalism, religion, and ethnicity under AKP government in Turkey / Sinem Adar -- Binding institutions : peasants and nation-state rule in the Albanian highlands, 1919-1939 / Besnik Pula -- Parameters of a postcolonial sociology of the Ottoman empire / Fatma Müge Göçek -- Orientalist-Eurocentric framing of sociology in India : a discussion on three twentieth-century sociologists / Sujata Patel -- A sociological breakthrough, not a sociological guilt trip / Mustafa Emirbayer -- Critical interventions in Western social theory : reflections on power and Southern theory / Patricia Hill Collins -- Connell and postcolonial sociology / Raka Ray -- Theoretical labors necessary for a global sociology : critique of Raewyn Connell's Southern theory / Isaac Ariail Reed -- Under southern skies / Raewyn Connell.
Includes index.
Print version record
Keywords: Social Science -- Sociology -- General; Political Science -- History & Theory; Social theory; Sociology; Political sociology; Power (Social sciences); Postcolonialism